2022
DOI: 10.52547/rbmb.10.4.537
|View full text |Cite
|
Sign up to set email alerts
|

Lectin-Like OLR1 3′UTR Rs1050286 Gene Polymorphism and Plasma Oxidized-LDL in Coronary Artery Disease and Their Relation to Cardiovascular Risk and Outcomes

Abstract: Background: Oxidized low-density lipoprotein (ox-LDL) has an important role in the genesis of coronary atherosclerosis. Lectin-like ox-LDL receptor 1 (OLR1) contributes to the uptake and internalization of ox-LDL. Genetic polymorphisms have been associated with coronary artery disease (CAD). Here we explore the association of plasma levels of ox-LDL and 3′ UTR OLR1 (rs1050286) SNP with CAD risk and inhospital adverse outcomes. Methods: A case-control study enrolled 192 patients with ST-segment elevation myocar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…OLR1 is also related to the with the storage of triacylglycerol, and is generally highly expressed in the lungs, liver, and adipose tissue ( Sun, Liu & Zhang, 2009 ; Catar et al., 2022 ). In recent years, OLR1 research has mainly focused on cardiovascular and metabolic diseases, such as atherosclerosis and diabetes ( Mohammed et al, 2022 ). In addition, several studies have shown that OLR1 may also be involved in the incidence and improvement of cancer, in particular tumour metastasis ( Jiang et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…OLR1 is also related to the with the storage of triacylglycerol, and is generally highly expressed in the lungs, liver, and adipose tissue ( Sun, Liu & Zhang, 2009 ; Catar et al., 2022 ). In recent years, OLR1 research has mainly focused on cardiovascular and metabolic diseases, such as atherosclerosis and diabetes ( Mohammed et al, 2022 ). In addition, several studies have shown that OLR1 may also be involved in the incidence and improvement of cancer, in particular tumour metastasis ( Jiang et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%